Human Induced Pluripotent Stem Cells for Inherited Cardiovascular Diseases Modeling - Jiang, Wenjian; Lan, Feng; Zhang, Hongjia (Current Stem Cell Research & Therapy, 2016)
Cardiovascular cells derived from patient specific induced Pluripotent Stem Cell (iPSC) harbor gene mutations associated with the pathogenesis of inherited cardiac diseases and congenital heart diseases (CHD). Numerous reports have demonstrated the utilization of human induced Pluripotent Stem Cell (hiPSC) to model cardiac diseases as a means of investigating their underlying mechanisms. So far, they have been shown to investigate the molecular mechanisms of many cardiac disorders, such as long-QT syndrome (LQT), catecholaminergic polymorphic ventricular tachycardia (CPVT), dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM), LEOPARD syndrome (LS), arrhythmogenic cardiomyopathy (ACM), Friedreich ataxia (FRDA), Barth syndrome (BTHS), hypoplastic left heart syndrome (HLHS), Marfan syndrome (MFS) and other CHD. This article summarizes the growing body of research related to modeling various cardiac diseases using hiPSCs. Moreover, by reviewing the methods used in previous studies, we propose multiple novel applications of hiPSCs to investigate comprehensive cardiovascular disorders and facilitate drug discovery.
Keywords: inherited arrhythmia